1988
DOI: 10.1016/0378-7206(88)90009-2
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility study in information systems: an analysis of criteria and contents

Abstract: Abstract:The feasibility study has been prescribed and described as an important step in information system development. Yet there has been little research on issues pertaining to its con-tents and criteria. This paper addresses these issues and reports research from a quasi-experimental investigation using actual system development projects. The empirical results show that the two most important factors in a feasibility study are: convincing the users that the system they get will actually meet their function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Some empirical studies have considered the identification of benefits. For example, a quasiexperimental study assessed the criteria and content of a feasibility study for IS development projects for industry and academia (Palvia & Palvia, 1988). The study identified criteria (e.g.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…Some empirical studies have considered the identification of benefits. For example, a quasiexperimental study assessed the criteria and content of a feasibility study for IS development projects for industry and academia (Palvia & Palvia, 1988). The study identified criteria (e.g.…”
Section: Empirical Studiesmentioning
confidence: 99%